2019
DOI: 10.1108/ijssp-10-2017-0141
|View full text |Cite
|
Sign up to set email alerts
|

The service sector: migration, technology and productivity

Abstract: Purpose The purpose of this paper is to study the characteristics of the workers in the informal economy and explore the reasons for workers migrating from rural to urban area. The authors also explore and enumerate various reasons why the migrants choose to work informally and study whether internal migrants treat this sector as temporary or transitory before moving to the formal sector. The authors reconnoitre the issues in coverage of factors in unregistered service, this research is carried out at a smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
1
0
2
Order By: Relevance
“…Additionally, Jha and Bag (2019) delved into the characteristics of workers in the informal economy, explored the reasons behind their choice to work in the informal sector, and examined whether such work is considered temporary or transitional before transitioning to the formal sector. Their findings indicated that the marginalization thesis is only partially accurate, as some migrants voluntarily enter this sector while others do so out of necessity.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…Additionally, Jha and Bag (2019) delved into the characteristics of workers in the informal economy, explored the reasons behind their choice to work in the informal sector, and examined whether such work is considered temporary or transitional before transitioning to the formal sector. Their findings indicated that the marginalization thesis is only partially accurate, as some migrants voluntarily enter this sector while others do so out of necessity.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…El sector de los servicios necesita instrumentos orientados a los problemas que se enfrentan como tiempo de trabajo (regulaciones del tiempo extra, periodos de descanso), la protección social (seguridad en el trabajo, la explotación) y la remuneración regular (escala de pago, planes de pensiones). Por otro lado podrían promover programas de formación en cooperación con los empleadores y los trabajadores de la organización, servicios de asesoramiento para aumentar la conciencia y mejorar la productividad (Jha & Bag, 2019).…”
Section: 2unclassified
“…O setor terciário é objeto de estudo a partir dos anos 30, e foi difundido por Fisher (1933) No entanto, apesar da importância crescente, os dados sobre prestação de serviços são tradicionalmente precários (Clark, 1984, Kon, 1999. Além de haver problemas quanto à falta de estatísticas comerciais e análises antecedentes, os quais poderiam subsidiar o desenvolvimento de pesquisas que auxiliem a compreender e na execução da atividade (Clark, 1984, Jha & Bag, 2019.…”
Section: Introductionunclassified